ANALISIS PEKERJAAN SUMBER DAYA MANUSIA (SDM) PADA LEMBAGA PENDIDIKAN ISLAM - Muhammad Rouf (Universitas Muhammadiyah Ponorogo, 2018)
Islamic Education Institutions really need to understand the importance of job analysis in its function for good organizational human resource management. If all school leaders apply human resource management, the management of the institution that relies on the figures will gradually shift towards a healthy organizational climate and rests on the work responsibilities of each of its employees. Discussion of this article includes the definition of HR employment analysis, the purpose of job analysis, the importance of job analysis, aspects of job analysis, job analysis techniques, and the relationship of job analysis with the function of human resource management. Job analysis is a systematic review process and collection of information in a systematic and comprehensive about the duties, obligations and responsibilities of employees in an organization, company or school. The purpose of Job analysis is oriented on how the workforce can perform its work effectively, efficiently and professionally. Identification of job specifications is important for teachers and all employees. The development of human resource skills can be done when the employees have done the work process while held regular evaluation. The aspects of human resource management are the output of work, the tasks performed, the structure of salaries, and the competence of the workers in doing their work. Techniques or ways of doing job analysis depend on the needs of the organization itself. However, the most important is the result of job analysis must be accurate and recorded neatly to be used as a reference in the process of human resource management next. Job analysis is carried out in the human resource management planning process. The results can then be used in the decision making of the entire human resource management process.